Behavior of Photosystems II and I Is Modulated Depending on N Partitioning to Rubisco in Mature Leaves Acclimated to Low N Levels and Senescent Leaves in Rice. (8th October 2022) - Suzuki, Yuji; Ohsaki, Kaho; Takahashi, Yuki; Wada, Shinya; Miyake, Chikahiro; Makino, Amane
Abstract: In mature leaves acclimated to low N levels and in senescent leaves, photosystems II and I (PSII and PSI, respectively) show typical responses to excess light energy. As CO2 assimilation is not transiently suppressed in these situations, the behavior of PSII and PSI is likely caused by endogenous biochemical changes in photosynthesis. In this study, this subject was studied in rice ( Oryza sativa L.). Analysis was performed on mature and senescent leaves of control and N-deficient plants. Total leaf-N, Rubisco and chlorophyll (Chl) levels and their ratios were determined as biochemical parameters of photosynthesis. Total leaf-N, Rubisco and Chl levels decreased in the mature leaves of N-deficient plants and senescent leaves. The percentage of Rubisco-N in the total leaf-N decreased in these leaves, whereas that of Chl-N tended to remain almost constant in mature leaves but increased in senescent leaves. Changes in PSII and PSI parameters were best accounted for by the Rubisco-N percentage, strongly suggesting that the behavior of PSII and PSI is modulated depending on changes in N partitioning to Rubisco in mature leaves acclimated to low N levels and in senescent leaves. It is likely that a decrease in N partitioning to Rubisco leads to a decrease in Rubisco capacity relative to other photosynthetic capacities that inevitably generate excess light energy and that the operation of PSII and PSI is modulated in such situations.